To the issue of inspection of Іnternet pages’ content by the parties of criminal proceedings - Малахова , О. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The article is devoted to research of the legal order of the use of information obtained from the Internet, in the criminal procedural proving. It was determined that the Criminal Procedural Code of Ukraine does not provide a legal identification and recording of information from web pages the access to which is not restricted by the system’s owner, possessor or keeper, or is not related to circumventing a system of logical protection. The receipt of such information cannot be accessed by removing Collecting information from electronic information systems, because the procedure for identifying and fixing such data are not associated with overcoming the protection of information from interference by other persons, and therefore not to the essence of covert investigative (detective) actions. This type of information should be identified and recorded by conducting such investigative (search) actions, as inspection. Analysis of judicial practice gives reason to conclude that the prosecution inspects the content of web pages during the pre-trial investigation, despite the fact that the criminal procedure code of Ukraine does not provide a procedure for this operation. The adversarial nature of criminal proceedings necessitates to provide the right of defender to inspect web pages the access to which is not restricted by the system’s owner, possessor or keeper, or is not related to circumventing a system of logical protection. The course and results of inspection of web pages shall be entered in the record. Therefore, it is necessary to give the defender the right to make the record. Inspection of web pages shall be accompanied by continuous video recording. Investigator, prosecutor, defender must provide a printed web page and its screenshots on an electronic device to record of inspection.

Визначено можливості використання у кримінальному процесуальному доказуванні відомостей, одержаних з мережі Інтернет. Досліджено правовий порядок одержання інформації з Інтернет простору відповідно до КПК України. Проаналізовано судову практику використання у кримінальному провадженні фактичних даних, отриманих з мережі Інтернет. Запропоновано надати захиснику право проводити огляд Інтернет-сторінок, доступ до яких не обмежений. Запропоновано правовий порядок виявлення та фіксації відомостей з мережі Інтернет, доступ до яких не обмежений.
ДО ПИТАННЯ ОГЛЯДУ СТОРОНАМИ КРИМІНАЛЬНОГО ПРОВАДЖЕННЯ ЗМІСТУ ІНТЕРНЕТ-СТОРІНОК
Keywords: Internet; proving; inspection; defender; adversarial.; Інтернет; доказування; огляд; захисник; змагальність.